Conservation of Andun Dance In The Community South Bengkulu - Haryani, Hafiidha Gusti; Elida, Elida (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2024)
The Andun dance is a traditional art form, cultural heritage, and religious practice of the people of South Bengkulu. It is an integral part of their social fabric, embodying Islam and preserving their unique customs. Despite its modernization, the Andun dance remains an essential component of marriage ceremonies, which are traditionally held over seven days and seven nights. While some may perceive these lengthy processes as excessive and time-consuming, they are deeply ingrained in the community’s traditions. Despite its significance, the Andun dance has faced challenges in maintaining its relevance and popularity among younger generations. This research aims to address this issue by exploring the preservation efforts being made by the government, community, and artists. The government organizes festivals, performances, and educational programs to promote the Andun dance, while schools incorporate it into their extracurricular activities. Community members actively participate in deliberations to ensure that the dance is accessible to the middle and lower socioeconomic classes. Artists provide coaching and training to their students, fostering the development of the Andun dance.